(untitled) (Raparin Journal of Humanities (RJH), 2021)
In the revolutions of history, an individual or leader is always given a higher role than all perpetrators of events, leaders have always been recognized as heroes in history, and a leader has faced all the factors of success and failure. In all societies, one or more people have always appeared and dominated the entire political and economic spheres of the country, a factor in the self-perception of history, or the hegemony of history, while the achievements of history belong only to one or the first leader, the total number of participants in the process of changing roles and his Impact on the direction of events. Abdul Karim Qasim is an example of a leader in Iraq who went from revolution to dictatorship, while people looked at him with hope and described him as a leader who changed the course of history, the reason for his failure was the conflict between political parties and the international community. This study is the gateway to getting to know Abdul Karim Qasim’s personality from the point of view of his opponents. In this two-part study, we discussed the beginnings of Abdul-Karim Qasim’s relations with political parties, and the views of the nationalist and communist parties towards Abdul-Karim Qasim, relying on several sources of different ideologies.